Genome-wide transcriptome profiling of nitrogen fixation in Paenibacillus sp. WLY78 - Shi, Hao-wen (BMC Microbiol, 2016)
BACKGROUND: Diazotrophic (nitrogen-fixing) Gram-positive and endospore-formed Paenibacillus spp. have potential uses as a bacterial fertilizer in agriculture. The transcriptional analysis of nitrogen fixation in Paenibacillus is lacking, although regulation mechanisms of nitrogen fixation have been well studied in Gram-negative diazotrophs. RESULTS: Here we report a global transcriptional profiling analysis of nitrogen fixation in Paenibacillus sp. WLY78 cultured under N(2)-fixing condition (without O(2) and NH(4)(+)) and non-N(2)-fixing condition (air and 100 mM NH(4)(+)). The nif (nitrogen fixation) gene operon composed of 9 genes (nifBHDKENXhesAnifV) in this bacterium was significantly up-regulated in N(2)-fixing condition compared to non-N(2)-fixing condition, indicating that nif gene transcription is strictly controlled by NH(4)(+) and O(2). qRT-PCR confirmed that these nif genes were differently expressed. Non-nif genes specifically required in nitrogen fixation, such as mod, feoAB and cys encoding transporters of Mo, Fe and S atoms, were coordinately transcribed with nif genes in N(2)-fixing condition. The transcript abundance of suf operon specific for synthesis of Fe-S cluster was up-regulated in N(2)-fixing condition, suggesting that Sul system, which takes place of nifS and nifU, plays important role in the synthesis of nitrogenase. We discover potential specific electron transporters which might provide electron from Fe protein to MoFe protein of nitrogenase. The glnR whose predicted protein might mediate nif transcription regulation by NH(4)(+) is significantly up-regulated in N(2)-fixing condition. The transcription levels of nitrogen metabolism and anaerobic respiration were also analyzed. CONCLUSIONS: The nif gene operon (nifBHDKENXhesAnifV) in Paenibacillus sp. WLY78 is significantly up-regulated in N(2)-fixing condition compared to non-N(2)-fixing condition. Non-nif genes specifically required in nitrogen fixation were also significantly up-regulated in N(2)-fixing condition. Fur and Fnr which are involved in anaerobic regulation and GlnR which might mediate nif gene transcription regulation by NH(4)(+) were significantly up-regulated in N(2)-fixing condition. This study provides valuable insights into nitrogen fixation process and regulation in Gram-positive firmicutes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-016-0642-6) contains supplementary material, which is available to authorized users.